Konstruksi Sosial Peran Gender dan Kedudukan Sosial Komunitas Nelayan di Desa Tasik Agung - Azzahid, Hasib Widya; Rano, Rano (IJTIMAIYA: Journal of Social Science and Teaching, 2025)
This study aims to determine the social construction of gender roles in fishing communities and the impact of gender role construction on the social position of fishing communities in Tasik Agung Village. The research method uses a descriptive qualitative approach. The collection techniques were participatory observation, in-depth interviews and documentation. Analysis Gender Harvard (Harvard Analytical Framework / Harvard Gender Analysis). The results showed that gender roles in fishing communities are formed through local cultural values that regulate the division of labor and social responsibilities between men and women. Although men predominantly serve as the main breadwinners through fishing activities, women also play strategic roles in the household economy and seafood processing. However, women's representation in community power structures remains limited, and their access to resources and decision-making spaces tends to be lower than that of men. This social construction contributes to social stratification that is not fully equal. Therefore, understanding gender relations in coastal communities is important as a basis for encouraging more inclusive and gender-equitable fisher empowerment policies.